Effect of sculling propulsion on body kinematics in displacement - Arelano, R.; Lopez-Contreras, G.; De La Fuente, B.; Morales, E.; Taladriz, S.; Gomes, L. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Swimming propulsion and its effect on body kinematics (displacement, velocity and acceleration) have been studied in different swimming phases (such as pull and push in freestyle) and the resultant changes in the swimmer's body velocity (CM or hip). Sculling is a basic propulsive action with four hand movements: outsweep, supination, insweep and pronation. 3D analysis showed a zigzag path, where hand displacement is mostly forward, with strong hand rotations during the change of direction (Arellano 2011). The in-depth study of this propulsive action includes kinematics of the and, flow visualisation and PIV in the typical situations: hovering and displacement (Arellano & Pardillo 2007). To understand the full effect of propulsion- quasisteady and unsteady (Arellano et al. 2006) we can measure the body displacement produced and its acceleration. This can provide a link between propulsive mechanisms and their effect on the body in a basic and experimentally controlled sculling action, easier to perform than full stroke propulsion. Considering the full body static during the performance of trials (as can be seen in Figure 1), body drag can be obtained, in a similar situation to previous studies on gliding, body drag after the second gliding position of the breaststroke underwater stroke applying inverse dynamics (Vilas-Boas et al. 2010). lt is possible to calculate the resultant force applying the equation P-D=ma (Vogel1994), knowing body acceleration and mass. The aim of the study was to know the effect of sculling propulsion on body kinematics in displacement and hence the resulting force in each propulsive phase of the sculling action.